2009
DOI: 10.1017/s1461145709000285
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases A and C in post-mortem prefrontal cortex from persons with major depression and normal controls

Abstract: Major depression (MDD) is a common and potentially life-threatening condition. Widespread neurobiological abnormalities suggest abnormalities in fundamental cellular mechanisms as possible physiological mediators. Cyclic AMP-dependent protein kinase (also known as protein kinase A [PKA]) and protein kinase C (PKC) are important components of intracellular signal transduction cascades that are linked to g-coupled receptors. Previous research using both human peripheral and post-mortem brain tissue specimens sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 51 publications
0
33
1
1
Order By: Relevance
“…cAMP/PKA signal transduction pathways have also been shown to be reduced in postmortem brain tissue from depressed patients (Shelton et al, 2009). …”
Section: Neuroendocrine Targetsmentioning
confidence: 99%
“…cAMP/PKA signal transduction pathways have also been shown to be reduced in postmortem brain tissue from depressed patients (Shelton et al, 2009). …”
Section: Neuroendocrine Targetsmentioning
confidence: 99%
“…1 has revealed massively increased ADH and ADHR in Asthma + PS group, considering that the well-known ADHR subtypes (V1A, V1B, and V2) are members of the seven transmembrane domain G-protein-coupled receptor superfamily [34], and PKA/PKC are involved in cell signaling pathways linked to G-protein-coupled receptors [23], thus, ADHR antagonists were employed to explore the potential link between ADH and PKA/ PKC in psychological stress asthma. In view of the potential regulatory network between ADHR subtypes (V1A, V2) and PKA/PKC in vascular smooth muscle cell (VSMC) [35] and other cells [36, 37], SR-49059 (V1A antagonist) and SR-121463A (V2 antagonist) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ADH has been proven to exert effects through binding to ADHR, primarily V1A and V2 receptors [16, 42]. Given that common ADHR subtypes (V1A, V1B, and V2) are members of the seven transmembrane domain G-protein-coupled receptor superfamily [34], and the significant participation of PKA and PKC in cell signaling pathways linked to G-protein-coupled receptors [23], the hypothesis was tested whether PKA and PKC were associated with ADH in psychological stress asthma, as studied using two different ADHR antagonists. We observed that ADHR antagonists signally suppressed higher protein levels of PKAα and PKCα after psychological stress stimulation as compared to OVA alone, indicating the correlation between ADH and PKA/PKC in psychological stress asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations